The Christian conception of divine revelation - Brînzea, Nicolae; Morcov, Elena (Technium Social Sciences Journal, 2023)
The fundamental idea of God's communication with people is expressed theologically and significantly through the concept of Revelation. In the continuous search for the truth about himself, the believer grows in knowledge and lives a complex human experience. He fulfills himself not only by the questions he asks, but also by the way he practically responds to divine love, which is manifested in the things and persons of the world and in the new circumstances created by God for each believer, adapted to his specific context. Thus, we believe that the world was created by the Word of God, and that all things came into being out of nothing, as stated in Hebrews 11, verse 3. As there is one God, the one and holy Trinity, there is also one Revelation. This Revelation is itself an eternally open reality in the divine-human sphere, culminating in the profound discovery of the Savior Jesus Christ. He is the Archetype through which the perfect epiphanic singularity manifests its fundamental attributes as expressed in the Chalcedonian formulation.